Evaluasi Galur Dihaploid Padi Terhadap Cekaman Salinitas - Azmi, Yudia (Menara Ilmu, 2018)
The purpose of this study was to obtain level of tolerance of rice strain to salinitystress (salt). Materials used in this experiment were NaCl, Yoshida media, 16 strains of riceplants and 2 strains as check plants (Pokkali and IR 29). The experiment was performentdusing complete randomized group design (RKLT) consisting of three replications. Each oneexperimental unit consists of four seeds of rice plants. Results of tolerant strains such as HS4-13-1-3, HS4-13-1-1, HS1-5-1-2, and HS3-15-1-8. The strains classified as moderate tolerantinclude HS1-28-1-1, HS1-28-1-2, HS1-35-1-2, HS1-35-1-4, HS1-35-1-8, HS1 -35-1-11, HS4-15-2-5, HS17-21-1-7, HS4-15-3-40, HS17-31-1-6, and HS17-62-1-2. While the sensitivestrain is HS17-1-1-2.Keywords: Nutrient culture; rice; salinity; tolerant